PENGARUH HARGA DAN MODEL TERHADAP KEPUASAN KONSUMEN KAOS SABLON DI KAWASAN MALIOBORO YOGYAKARTA - Rusli, Wendri (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2013)
This research aimed to prove that consumer satisfaction to singlet that is on the market at Malioboro Yogyakartas area regarded by factor price and model. At deep observational being done to 100 respondents have already buy and have once had templet singlets. Utilizing computer with SPSS 13.0 for is windows o analisis by uses bifilar linear regression to be gotten price result and positive ascendant model and signifikan to consumer decision. Done by quiz t and quiz f signifikans ala and unsures positive price and model regards consumer decision. Be of yielding beta coefficient quiz gotten by factor decision dominant buys to be regarded by model.